ASSOCIATION OF PTSD SYMPTOMS WITH THE QUALITY OF LIFE IN THE CONFLICT AFFECTED PEOPLE IN NORTH HALMAHERA - Blandina, Olivia Asih (Hibualamo : Seri Ilmu-Ilmu Alam dan Kesehatan, 2017)
Political instability, civil conflict, war, genocide, persecution, and the attendant violations of human rights are increasingly recognized as paramount public health concerns (Marshall et al, 2005). Conflicts in various regions in Indonesia so far has led to its own social problems, such as the buildup of refugees, social cleavage which causes crisis social, poverty, unemployment, and limited access for the poor in resources. According to the United Nations High Commissioner on Refugees, there were approximately 19.2 million refugees, internally displaced persons, and asylum seekers worldwide in 2004 (Marshall et al., 2005). In the Consolidated Inter-Agency Appeal for Indonesia in 2003, noted that the number of people who are very affected by various conflicts since 1999 to reach 3 million people, while the vulnerable groups to reach 40 million people, or one-fifth of the entire population of Indonesia. Exposure to conflict has been associated with lower quality of life (QoL) even after the end of the actual hostilities. The effects of war-related events may persist for many years. Several studies have suggested that trauma is associated with physical as well as mental health problems, especially post-traumatic stress disorder (Krause, 2014). Posttraumatic stress disorder has been found to be associated with decreased quality of life, poorer physical health, and problems with social functioning (Steel et al., 2011). The research design is cross sectional design. This design is best suited to studies aimed at finding out the prevalence of a phenomenon, situation, problem, attitude or issue, by taking a cross-section of the population.